1997
DOI: 10.1029/96wr03851
|View full text |Cite
|
Sign up to set email alerts
|

The influence of physical heterogeneity on microbial degradation and distribution in porous media

Abstract: Abstract. Intermediate-scale experiments (meter-long, two-dimensional flow cell) were performed with aerobic biodegradation of benzoate substrate in physically heterogeneous (bimodal inclusive) media. Clastic heterogeneities were represented in a quasi-twodimensional field, with low-conductivity inclusions embedded in a high-conductivity sandy matrix. The two media had similar pore-scale dispersivities but the conductivity ratio (•1:50) incurred macrodispersive spreading in the longitudinal direction. The high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 56 publications
3
112
1
Order By: Relevance
“…1, [169]), similar to observations in field bioremediation efforts (US DOE, 1993). Column experiments have suggested that the response observed in [169] may be cell-division mediated transport, a mechanism long recognized in the microbiology literature [60,99,161,179]. Cell-division mediated transport has also been referred to as mother-daughter or shedding cells and is when the ''mother'' cell, attached perpendicular to the mineral surface, grows, divides, and the ''daughter'' cell is released into the aqueous phase [163].…”
Section: Metabolic Effects On Microbial Transportmentioning
confidence: 99%
See 4 more Smart Citations
“…1, [169]), similar to observations in field bioremediation efforts (US DOE, 1993). Column experiments have suggested that the response observed in [169] may be cell-division mediated transport, a mechanism long recognized in the microbiology literature [60,99,161,179]. Cell-division mediated transport has also been referred to as mother-daughter or shedding cells and is when the ''mother'' cell, attached perpendicular to the mineral surface, grows, divides, and the ''daughter'' cell is released into the aqueous phase [163].…”
Section: Metabolic Effects On Microbial Transportmentioning
confidence: 99%
“…Therefore, in unstructured models the biomass is a fully penetrable volumeless component which assumes that a linear relation exists between mass of substrate consumed and mass of biomass produced and that no diffusion limitations affect the transfer of substrate mass from solution into the biomass. This approach has been taken in model construction [25,144,159,162], in column studies that focus on bacterial transport [69,120] and in intermediate-scale flow cell studies that focus on active degradation and growth and coupled transport [130,169]. For instance, Macquarrie et al [162] used this approach in treating biomass involved in aerobic degradation as a volumeless species undergoing transport, with equilibrium partitioning of biomass between aqueous and attached phases.…”
Section: Conceptual and Mathematical Representation Of Subsurface Biomentioning
confidence: 99%
See 3 more Smart Citations